Effects of Alcohol and Estrogen Receptor Blockade Using ICI 182, 780 on Bone in Ovariectomized Rats. (17th September 2019) - Wagner, Lindsay; Howe, Kathy; Philbrick, Kenneth A.; Maddalozzo, Gianni F.; Kuah, Amida F.; Wong, Carmen P.; Olson, Dawn A.; Branscum, Adam J.; Iwaniec, Urszula T.; Turner, Russell T.
Abstract : Background: Estrogen signaling is essential for the sexual dimorphism of the skeleton, is required for normal bone remodeling balance in adults, and may influence the skeletal response to alcohol. High levels of alcohol consumption lower bone mass in ovary‐intact but not ovariectomized (ovx) rats. However, the extremely rapid rate of bone loss immediately following ovx may obscure the effects of alcohol. We therefore determined (i) whether heavy alcohol consumption (35% caloric intake) influences bone in sexually mature ovx rats with established cancellous osteopenia and (ii) whether ICI 182, 780 (ICI), a potent estrogen receptor signaling antagonist, alters the skeletal response to alcohol. Methods: Three weeks following ovx, rats were randomized into 5 groups, (i) baseline, (ii) control + vehicle, (iii) control + ICI, (iv) ethanol (EtOH) + vehicle, or (v) EtOH + ICI, and treated accordingly for 4 weeks. Dual‐energy X‐ray absorptiometry, microcomputed tomography, blood measurements of markers of bone turnover, and gene expression in femur and uterus were used to evaluate response to alcohol and ICI. Results: Rats consuming alcohol had lower bone mass and increased fat mass. Bone microarchitecture of the tibia and gene expression in femur were altered; specifically, there was reduced accrual of cortical bone, net loss of cancellous bone, and differential expression of 19/84 genes related to bone turnover. Furthermore, osteocalcin, a marker of bone turnover, was lower in alcohol‐fed rats. ICI had no effect on weight gain, body composition, or cortical bone. ICI reduced cancellous bone loss and serum CTX‐1, a biochemical marker of bone resorption; alcohol antagonized the latter 2 responses. Neither alcohol nor ICI affected uterine weight or gene expression. Conclusions: Alcohol exaggerated bone loss in ovx rats in the presence or absence of estrogen receptor blockade with ICI. The negligible effect of alcohol on uterus and limited effects of ICI on bone in alcohol‐fed ovx rats suggest that estrogen receptor signaling plays a limited role in the action of alcohol on bone in a rat model for chronic alcohol abuse. Abstract : There is controversy regarding the role of estrogen signaling in mediating the skeletal response to alcohol. Microcomputed tomography revealed that ethanol consumption at high levels results in cancellous bone loss in estrogen‐depleted (ovariectomized) rats in the presence or absence of the estrogen receptor antagonist ICI 182, 780 (ICI) (see Figure). These results suggest that ethanol‐induced changes in estrogen signaling play a limited role in mediating the detrimental effects of alcohol on bone in a rat model for chronic alcohol abuse.